Analisis, Desain dan Rancang Bangun Sistem Informasi Akademik Mobile Berbasis Android - Setiawan, Dedy; Suratno, Tri; Lutfi, Lutfi (ELKHA : Jurnal Teknik Elektro, 2018)
Abstract The purpose of this study was to analyze and to design an Android-based academic information system at Jambi University. This information system would be able to help the activities of the civitas academica at Jambi University. This information system has important facilities in the form of course contract features, view study results, input courses, input grades, lecture schedules and class schedule information. When developed this system, researcher used the Java programming language, where Java programming is used to build android-based applications, while for this database information system used MySQL. Analysis method and system design in this research used the Waterfall method. The Waterfall method has several stages: Analysis, System Design, Implementation, Integration, Operation and Maintenance. In the process of data collection, researcher used methods of observation, interview and literature studies. The output of this research is an Android-based academic information system.Â Keyword - Academic Information System, Android, Waterfall